Efficacy of Fosfomycin and Its Combination With Aminoglycosides in an Experimental Sepsis Model by Carbapenemase-Producing Klebsiella pneumoniae Clinical Strains - Cebrero-Cangueiro, Tania; Labrador-Herrera, Gema; Pascual, Álvaro; Díaz, Caridad; Rodríguez-Baño, Jesús; Pachón, Jerónimo; del Palacio, José P.; Pachón-Ibáñez, María E.; Conejo, M. Carmen (Frontiers in Medicine, 2021)
Carbapenemase-producing Klebsiella pneumoniae infections are an increasing global threat with scarce and uncertain treatment options. In this context, combination therapies are often used for these infections. The bactericidal and synergistic activity of fosfomycin plus amikacin and gentamicin was studied trough time–kill assays against four clonally unrelated clinical isolates of carbapenemase-producing K. pneumoniae, VIM-1, VIM-1 plus DHA-1, OXA-48 plus CTXM-15, and KPC-3, respectively. The efficacy of antimicrobials that showed synergistic activity in vitro against all the carbapenemase-producing K. pneumoniae were tested in monotherapy and in combination, in a murine peritoneal sepsis model. In vitro, fosfomycin plus amikacin showed synergistic and bactericidal effect against strains producing VIM-1, VIM-1 plus DHA-1, and OXA-48 plus CTX-M-15. Fosfomycin plus gentamicin had in vitro synergistic activity against the strain producing KPC-3. In vivo, fosfomycin and amikacin and its combination reduced the spleen bacterial concentration compared with controls groups in animals infected by K. pneumoniae producing VIM-1 and OXA-48 plus CTX-M-15. Moreover, amikacin alone and its combination with fosfomycin reduced the bacteremia rate against the VIM-1 producer strain. Contrary to the in vitro results, no in vivo efficacy was found with fosfomycin plus amikacin against the VIM-1 plus DHA-1 producer strain. Finally, fosfomycin plus gentamicin reduced the bacterial concentration in spleen against the KPC-3 producer strain. In conclusion, our results suggest that fosfomycin plus aminoglycosides has a dissimilar efficacy in the treatment of this severe experimental infection, when caused by different carbapenemase-producing K. pneumoniae strains. Fosfomycin plus amikacin or plus gentamycin may be useful to treat infections by OXA-48 plus CTX-M-15 or KPC-3 producer strains, respectively.